Success Rate of Probing for Congenital Nasolacrimal Duct Obstruction at Various Ages - Perveen, Semi (Ophthalmic Research Center, 2014)
PURPOSE: To determine the success rate of probing for congenital nasolacrimal duct obstruction (CNLDO) in various age groups. METHODS: One hundred children (118 eyes) aged 4 to 48 months diagnosed with CNLDO were included and divided into 6 groups; group 1: infants 4-6 months of age, group 2: infants from 7 to 12 months, group 3: toddlers 13-18 months of age, group 4: older toddlers 19-24 months old, group 5: children from 25 to 36 months, and group 6: children 37-48 months of age. Probing was performed under general anesthesia in all subjects. All patients were followed at regular intervals up to 6 months postoperatively. Successful probing was documented as complete remission of symptoms 2 weeks following the procedure. RESULTS: The success rate of probing was 100% (2 eyes) in group 1, 94% (47 eyes) in group 2, 84.4% (27 eyes) in group 3, 83.3% (15 eyes) in group 4, 61.5% (8 eyes) in group 5 and 33.3% (1 eye) in group 6; the overall success rate was 84.7% (100 eyes). The majority of eyes, 87.3% (103 eyes), had membranous obstruction while 12.7% (15 eyes) had firm obstruction. The success rate was 92.2% (95 eyes) in eyes with membranous obstruction and 33.3% (5 eyes) in those with firm obstruction. CONCLUSION: Probing of the nasolacrimal duct under general anesthesia is a safe and viable option as a primary treatment modality for CNLDO. The success rate decreases with increasing age; membranous obstruction resolves in the majority of cases whereas firm obstruction has a poorer outcome.